Effects of decentralization on school resources: Sweden 1989-2002 - Eva Mörk; Åsa Ahlin (Uppsala University, Department of Economics, 2007)
Sweden has undertaken major national reforms of its school sector which, consequently, has been classified as one of the most decentralized ones in the OECD. This paper investigates whether school resources became more unequally distributed across municipalities in connection with the reforms and if local tax base, grants, and preferences affected local school resources differently as decentralization took place. Using municipal data the paper studies how per pupil spending and the teacher-pupil ratio has evolved over the period 19892002, separating between three different waves of decentralization. As nothing much has happened with per pupil spending, the teacher-pupil ratio has become more evenly distributed across municipalities. Municipal tax base affects per pupil spending in the same way regardless of whether the school sector is centralized or decentralized, but has a smaller effect on teacher-pupil ratio after the reforms. The less targeted grants are, the fewer teachers per pupil do the municipalities employ. The results for local preferences are less clear cut.
urn:nbn:se:uu:diva-25383
Keywords: H40; H52; H70; 330; school resources; school finance reform; decentralization; grant reform; Schulpolitik; Schulfinanzierung; Bildungsreform; Dezentralisierung; Schweden